Structure of antiviral drug bulevirtide bound to hepatitis B and D virus receptor protein NTCP - Liu, Hongtao; Zakrzewicz, Dariusz; Nosol, Kamil; Irobalieva, Rossitza N.; Mukherjee, Somnath; Bang-Sørensen, Rose; Goldmann, Nora; Kunz, Sebastian; Rossi, Lorenzo; Kossiakoff, Anthony A.; Urban, Stephan; Glebe, Dieter; et al. (Nature Communications, 2024)
Cellular entry of the hepatitis B and D viruses (HBV/HDV) requires binding of the viral surface polypeptide preS1 to the hepatobiliary transporter Na+-taurocholate co-transporting polypeptide (NTCP). This interaction can be blocked by bulevirtide (BLV, formerly Myrcludex B), a preS1 derivative and approved drug for treating HDV infection. Here, to elucidate the basis of this inhibitory function, we determined a cryo-EM structure of BLV-bound human NTCP. BLV forms two domains, a plug lodged in the bile salt transport tunnel of NTCP and a string that covers the receptor’s extracellular surface. The N-terminally attached myristoyl group of BLV interacts with the lipid-exposed surface of NTCP. Our structure reveals how BLV inhibits bile salt transport, rationalizes NTCP mutations that decrease the risk of HBV/HDV infection, and provides a basis for understanding the host specificity of HBV/HDV. Our results provide opportunities for structure-guided development of inhibitors that target HBV/HDV docking to NTCP.
Gesehen am 09.07.2024